2018
DOI: 10.1108/jsit-03-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between system quality, service quality, and customer satisfaction

Abstract: Purpose This study aims to explore the impact of system quality dimensions, namely, ease of use, accessibility, interactivity and website innovativeness on service quality (SQ) and customer satisfaction. Design/methodology/approach The study used a quantitative approach, by using a survey method. The unit of analysis was the individual. A total of 618 questionnaires were randomly distributed to university students and staff in Jordan. The partial least square path-modeling method was used in the estimation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 71 publications
(103 reference statements)
2
25
0
5
Order By: Relevance
“…M-commerce is changing the way of trading globally by using the Internet for commerce, including purchasing and selling goods and services, after-sales services, and assistance [22,23]. However, this transition is growing at different rates in different parts of the world [24][25][26]. Asia, the USA, and Northern Europe are currently facing a rapid growth of m-commerce compared to other parts of the world [23,27].…”
Section: M-commerce Advantages and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…M-commerce is changing the way of trading globally by using the Internet for commerce, including purchasing and selling goods and services, after-sales services, and assistance [22,23]. However, this transition is growing at different rates in different parts of the world [24][25][26]. Asia, the USA, and Northern Europe are currently facing a rapid growth of m-commerce compared to other parts of the world [23,27].…”
Section: M-commerce Advantages and Challengesmentioning
confidence: 99%
“…For one, social media channels are particularly popular with younger users as a shopping platform [18,31,32]. At the same time, security, credibility, and trust are essential [7,8,26,33,34]. Companies are storing large amounts of data being worrisome amongst consumers regarding personal privacy [35,36].…”
Section: M-commerce Advantages and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive and direct impact of SQ on CS and PI is shown in several studies. In the mobile commerce context, Anas et al, (2018) and Sukanya and Saroj (2015) revealed that SQ affects the CS positively and significant relationship. Karin (2019) and Yousef and Dariyoush (2018) found the presence of a significant and positive relationship between SQ and PI.…”
Section: Service Quality (Sq)mentioning
confidence: 99%
“…Previous studies have examined a range of factors influencing consumer behaviour in different context. These include service quality (Rita et al, 2019;Mohammad Salameh et al, 2018), perceived value (Liu et al, 2015;Carlson et al, 2015) and trust (Artigas & Barajas-Portas, 2019;Trivedi & Yadav, 2020). However, there have been few attempts to comprehensively examine consumer behaviour in mobile shopping context.…”
Section: Introductionmentioning
confidence: 99%